Emotional Intelligence in the Perspective of Hadith: An Analysis of Emotion Regulation and Its Implementation in Character Education - SHOLAHUDDIN, SHOLAHUDDIN; La Ode Ismail Ahmad; Abdul Rahman Sakka (At-Takwin: Journal of Islamic Education Studies, 2025)
This article aims to examine the concept of emotional intelligence from the perspective of the Prophet Muhammad’s saw. hadith and its implementation in education, particularly in character education at schools. Emotional intelligence includes the ability to recognize, regulate, and redirect emotions in a healthy and proportional manner. This study uses a qualitative approach with library research methods, drawing on authentic hadiths and relevant academic literature. The findings show that the Prophet saw. provided practical examples of recognizing and managing emotions through prayer, physical actions (such as remaining silent, sitting, lying down, and performing ablution), and offering new meaning to emotional situations. In educational practice, emotional intelligence can be instilled through teacher guidance, self-reflection routines, and spiritual approaches based on Islamic values. Therefore, the concept of emotional intelligence in hadith is highly relevant to strengthening holistic character education.